Modelling and optimization of polyphenol and antioxidant extraction from Rumex hastatus by green glycerol-water solvent according to response surface methodology - Nida Anis; Dildar Ahmed (Heliyon, 2022)
Rumex hastatus (RH) is an edible wild herb abundantly distributed in many parts of the world. With the increasing realization of the environmental threats corresponding to the use of conventional organic solvents, the realization to explore efficient green solvents for the extraction of valuable natural products from plants is increasing. The present project, therefore, aimed to discover an optimized efficient and green process for obtaining antioxidant phytochemicals from R. hastatus using aqueous glycerol as a green and low-cost extraction medium. For modelling and optimization according to RSM (response surface methodology), the independent factors were glycerol concentration, temperature and time, and the responses included TPC (total phenolic content), TFC (total flavonoid content), and anti-radical activity (ARA) and iron chelating activity (ICA). The predicted optimum conditions were 52.155% glycerol concentration, 41.303 min extraction time and 50 °C extraction temperature with the predicted values for TPC, TFC, ARA and ICA as 21.65 mg GA/g DW, 95.78 mg RE/g DW, 84.93% and 46.47%, respectively. For responses, well-fitted quadratic models were suggested. Thus, aqueous glycerol is an efficient, green, and cost-effective solvent and its around 50% solution can effectively be used as an extracting medium for antioxidants from R. hastatus. The discovered model should be viable for large scale extraction of bioactive compounds from this plant.